Forsythoside A protects against lipopolysaccharide-induced acute lung injury through up-regulating microRNA-124. Issue 19 (5th October 2020) - Lu, Zibin; Yang, Huayi; Cao, Huihui; Huo, Chuying; Chen, Yuyao; Liu, Dongyi; Xie, Pei; Zhou, Hongling; Liu, Junshan; Yu, Linzhong
Abstract: Acute lung injury (ALI) is a life-threatening disease without effective pharmacotherapies, so far. Forsythia suspensa is frequently used in the treatment of lung infection in traditional Chinese medicine. In search for natural anti-inflammatory components, the activity and the underlying mechanism of Forsythoside A (FA) from Forsythia suspensa were explored. In the present paper, BALB/c mice and murine RAW 264.7 cells were stimulated by LPS to establish inflammation models. Data showed that FA inhibited the production of TNF-α and IL-6 and the activation of STAT3 in LPS-stimulated RAW 264.7 cells. Additionally, FA increased the expression level of microRNA-124 (miR-124). Furthermore, the inhibitory effect of FA on STAT3 was counteracted by the treatment of miR-124 inhibitor. Critically, FA ameliorated LPS-induced ALI pathological damage, the increase in lung water content and inflammatory cytokine, cells infiltration and activation of the STAT3 signaling pathway in BALB/c mice. Meanwhile, FA up-regulated the expression of miR-124 in lungs, while administration with miR-124 inhibitor attenuated the protective effects of FA. Our results indicated that FA alleviates LPS-induced inflammation through up-regulating miR-124 in vitro and in vivo . These findings indicate the potential of FA and miR-124 in the treatment of ALI.